Iowa Birdline update, December 30-31, 1991 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1991)
Email of Iowa Birdline updates for December 30-31, 1991. The highlights for the update include sightings of a first-winter Glaucous Gull, two adult Golden Eagles and a Black-legged Kittiwake. Also included are handwritten notes with sightings of two possibly three Iceland Gulls, a Snowy Owl and a Pileated Woodpecker. Epson - sheet feed/flatbed